PENGEMBANGAN MEDIA AJAR TAR (TECHNOLOGY AUGMENTED REALITY) BERBASIS ULAR TANGGA PADA MATERI IPAS UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV SDN MOJOROTO 4 - Totti, Ilham Syah; Erwin Putera Permana; Agus Widodo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research focuses on observations at SDN Mojoroto 4, Kediri City, which indicate that the use of learning media for Natural Science and Social Science (IPAS) on the topic of Indonesia's Cultural Wealth is still suboptimal, relying more on textbooks and lectures. This has resulted in low interest and active participation from students. This study aims to develop a Technology Augmented Reality learning media based on a snake and ladder game for fourth-grade students, focusing on its validity, practicality, and effectiveness in enhancing students' learning interest.The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study are fourth-grade students, with data collected through observations, interviews, and validation questionnaires from subject matter experts, media experts, and interest in learning, as well as student response questionnaires. Data analysis is conducted using both qualitative and quantitative descriptive approaches, including N-Gain tests for effectiveness.The validation results show that the snake and ladder-based TAR learning media is highly valid, with validation scores of 88% from subject matter experts, 84% from media experts, and 95% from interest in learning experts, resulting in an overall average of 89%. In terms of practicality, student response questionnaires in the limited trial reached 90% and in the extensive trial 95%. For effectiveness, students' interest in learning increased from 65% to 85%, with an N-Gain score of 0.57, indicating that this learning media is quite effective in enhancing students' learning interest.